Coupling of SWMM With 2D Hydrodynamic Model for Simulation of Sponge City Construction Scheme. Issue 1 (January 2021) - Fan, Yuyan; Wang, Chengwen; Yu, Haijun; Pan, Junhao; Ouyang, Zilu
Abstract: Sponge city is a new urban stormwater management concept proposed by China to solve the urban water environment and security problems. The stormwater management model (SWMM) is one of the most commonly used urban stormwater and sponge city simulation models. SWMM is coupled with a two-dimensional hydrodynamic model based on the finite volume method to establish a coupled 1D and 2D hydrodynamic model in this research. The coupled model can simulate the drainage pipe network, sponge measures and flood inundation at the same time. A predictor-corrector method with good stability was used in the coupled model to ensure the non-negativity of the water volume of the 2D model cell. The sponge city construction scheme for a community in Beijing was simulated and analyzed using several design rainstorm processes with different return periods based on the proposed model. It is proved that the coupling model can be applied to sponge city construction problems and sponge measures can reduce the flood inundation and the load of drainage network system by simulating the drainage conditions and ground waterlogging before and after the reconstruction of the drainage community.